Testing compliance to WHO guidelines for physical activity in Flanders: insights from time-use diaries - Djiwo Weenas; Theun Pieter van Tienoven; Julie Verbeylen; Joeri Minnen; Ignace Glorieux (BMC, 2019)
Abstract Background Regular physical activity decreases the risk for numerous non-communicable diseases. The World Health Organization has suggested physical activity (PA) guidelines that, based on previous research, would provide health benefits to those who comply. The first guideline for health benefits suggests 150 min of moderate PA or equivalent per week. The guideline for additional health benefits suggests 300 min of PA or equivalent per week. The objective of this paper is to analyze to what extent these two WHO PA guidelines for adults are met in the Belgian region of Flanders. Furthermore, we are interested to see which groups are more or less likely to meet the PA guidelines. Methods Crosstables and logistic regressions are used on a sample of 3028 adults in the Belgian region of Flanders. All respondents filled in a 7-day time-diary in which they continuously recorded all their activities. Results Firstly, men are more likely than women to comply to both PA guidelines. Secondly, living with a partner increases the odds to comply to the guidelines. For men, this is the case for both guidelines, while for women, this only applies to the first guideline. Thirdly, women with a young child have lower odds to comply to the guidelines, while having a young child doesn't have an effect for men. Conclusion Previous research on meeting PA guidelines in Flanders shows diverging results. Time-diary data allows researchers to strictly follow the WHO definition when operationalizing compliance to PA guidelines. There is a need for future research that combines time-diaries with a PA questionnaire and accelerometer data to gain more insights on the benefits and pitfalls of both methodologies.